CD44: molecular interactions, signaling and functions in the nervous system - Dzwonek, Joanna; Wilczynski, Grzegorz M. (Frontiers in Cellular Neuroscience, 2015)
CD44 is the major surface hyaluronan receptor implicated in intercellular and cell-matrix adhesion, cell migration and signalling. It is a transmembrane, highly glycosylated protein with several isoforms resulting from alternative gene splicing. The CD44 molecule consists of several domains serving different functions: the N-terminal extracellular domain, the stem region, the transmembrane domain and the C-terminal tail. In the nervous system, CD44 expression occurs in both glial and neuronal cells. The role of CD44 in the physiology and pathology of the nervous system is not entirely understood, however, there exists evidence suggesting it might be involved in the axon guidance, cytoplasmic Ca2+ clearance, dendritic arborization, synaptic transmission, epileptogenesis, oligodendrocyte and astrocyte differentiation, post-traumatic brain repair and brain tumour development.